Reflections on English literature teaching in secondary high school. - Della Valle, Paola (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2014)
Reflections on English literature teaching in secondary high school. In Italian High Schools, literature in English is still often taught as the history of English literature, according to established tradition or convenience, although the Ministry of Education has given teachers ample freedom in the choice of texts, encouraging themes and genres close to students. The literary text most effectively contributes to improving the students’ knowledge of a foreign culture as well as their cultural awareness and critical abilities. A teacher course on the didactics of English literature must therefore help its participants to make the most of this extraordinary linguistic, cognitive and educative instrument, avoiding a reassuring but inefficient approach. My teaching experience in the TFA programme has pointed out that highly selected and linguistically proficient future teachers do not need to go through content again but should be freed from outdated teaching methods in favour of flexible and dynamic practices, including choice of appropriate and contextualised texts, interaction between text and reader, and connection of the text with the present and the students’ life. And the trainees may be surprised at the enormous possibilities of a faraway text such as Geoffrey Chaucer’s Canterbury Tales.